Purification Of The Multiwalled Carbon Nanotubes (Mwcnts) And The Application Of The 3r (Reduce, Reuse And Recycle) Concept On The Chitosan/Mwcnts Nanocomposites - Cheng, Yoke Kooi (2012)
The as-prepared multiwalled carbon nanotubes (MWCNTs) consist of high impurities of amorphous carbon, metal catalysts and catalyst support that impeded the MWCNTs applications. The combination of the wet etchant (0.2 M sodium citrate, 0.2 M NTANa3 and 0.1 M NaOH, in the volumetric ratio of 2:2:1) was used to remove the amount of impurities of the raw MWCNTs. Treatment temperature was the key factor for the effectiveness of the wet etchant on the removal of residue but it was not affected by the reaction time. Alumina, the major impurity was reduced from 24.0 wt. % to 9.3 wt. % whereas cobalt and molybdenum were reduced from 9.6 wt. % to 4.4 wt. % and 2.3 wt. % to 0.6 wt. %, respectively at temperature of 138oC in wet etchant treatment. With the aid of the piranha solution treatment, further reduced the impurities; alumina to 6.7 wt. %, cobalt to 0.7 wt. % and molybdenum to 0.1 wt. %. Although MWCNTs able to act as fiber to enhance mechanical properties of the polymer but they are harmful to the living. Hence, The 3R conceptual idea is used to overcome the limitation of the MWCNTs. The chitosan/MWCNTs nanocomposites were prepared by solution processing method.